PREVENTION OF SEXUAL HARASSMENT IN THE WORKPLACE: APPLICATION OF ARTIFICIAL INTELLIGENCE AND POWER FOR POLICY IMPLICATIONS - 1. Muskan Mandhyani , 2. Prof. (Dr.) Broto Rauth Bhardwaj (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This research paper delves into the multifaceted realm of the Prevention of Sexual Harassment (POSH) policy, dissecting its comprehensive framework, implementation strategies, and discernible impact within the workplace. The primary objective is to create and sustain a work environment that is not only healthy, safe, and productive but also free from discrimination and harassment. Emphasizing the prohibition and redressal of sexual harassment, the policy strives to maintain high ethical standards. The scope of the policy extends to all employees within the organization, with due regard for local laws taking precedence. Sexual harassment is meticulously defined, encompassing various forms of unwelcome behaviours, both verbal and nonverbal. The responsibilities entrusted to employees underscore the imperative to treat each other with dignity, refrain from any unwelcome behaviour with sexual connotations, and report incidents promptly. The policy establishes an Internal Complaints Committee (ICC) to address complaints confidentially and fairly. This committee comprises members with diverse backgrounds, emphasizing a three-year tenure, and follows stringent guidelines outlined in the POSH Act. The research scrutinizes the ICC’s eligibility, functioning, and the intricate process it follows, encompassing stages like conciliation, inquiry, and actions during the pendency of an inquiry. Challenges and impacts associated with the implementation of the policy are explored, shedding light on barriers to reporting, organizational culture, and the broader economic, psychological, and professional repercussions on victims. The paper also investigates best practices, drawing on successful case studies and technological advancements that fortify prevention strategies. The research concludes with a synthesis of key findings, implications for future research and policy development, offering a holistic understanding of the POSH policy’s nuances and its profound implications on fostering safer, more equitable workplaces.